Small Size Dual-band Bandpass Filters with Multiconductor Transmission Lines and Shunt Open Stubs - Pérez-Escribano, Mario; Sánchez-Martínez, Juan José; Márquez Segura, Enrique (My University, 2018)
A dual-band bandpass filter consisting of multiconductor transmission lines (MTL) and shunt stubs has been designed. The used topology, based on the interconnection of two identical MTL and a shunt open stub, has a frequency response that can be modelled by using the generalized Chebyshev functions. A prototype of a 4 fingers-MTL is manufactured and measured and a good agreement between analytical and measured results is obtained. Furthermore, it is easy to get a design criterion that enables getting good responses varying just a few parameters.
Keywords: Microondas; microwave; dual-band bandpass filter; multiconductor transmission line